2021
DOI: 10.1136/thoraxjnl-2020-216794
|View full text |Cite
|
Sign up to set email alerts
|

Timing ofMycobacterium tuberculosisexposure explains variation in BCG effectiveness: a systematic review and meta-analysis

Abstract: RationaleThe heterogeneity in efficacy observed in studies of BCG vaccination is not fully explained by currently accepted hypotheses, such as latitudinal gradient in non-tuberculous mycobacteria exposure.MethodsWe updated previous systematic reviews of the effectiveness of BCG vaccination to 31 December 2020. We employed an identical search strategy and inclusion/exclusion criteria to these earlier reviews, but reclassified several studies, developed an alternative classification system and considered study d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
(45 reference statements)
1
5
1
Order By: Relevance
“…A recent meta-analysis concluded that BCG confers protection against TB shortly after vaccination, and hence, its effect is most notable in children but not in adults in high burden settings. Their results in adults do not support our findings, but there is limited data in individuals beyond 60 years of age [47]. Confirmation of our findings in other elderly cohorts would open the possibilities for considering a booster BCG in the elderly.…”
Section: Plos Onecontrasting
confidence: 95%
“…A recent meta-analysis concluded that BCG confers protection against TB shortly after vaccination, and hence, its effect is most notable in children but not in adults in high burden settings. Their results in adults do not support our findings, but there is limited data in individuals beyond 60 years of age [47]. Confirmation of our findings in other elderly cohorts would open the possibilities for considering a booster BCG in the elderly.…”
Section: Plos Onecontrasting
confidence: 95%
“…Our results are consistent with findings that BCG can sometimes provide long-term protection against human TB, and are consistent with studies showing BCG-mediated protection in individuals without prior Mtb exposure (tuberculin skin test-negative or IGRA-negative individuals) or in low Mtb transmission settings 1-4 . The low overall observed efficacy (∼13%) in preventing detectable infection also reflects the suboptimal nature of BCG-mediated immunity.…”
Section: Discussionsupporting
confidence: 92%
“…New and effective tuberculosis (TB) vaccines are urgently needed. Although BCG vaccination can provide protection in infants and older children in some clinical settings [1][2][3][4] , it has proven to be inadequate to combat the global pandemic. There are numerous TB vaccine candidates in the developmental pipeline 5 , but it will not be feasible to conduct human efficacy trials for most of them.…”
Section: Introductionmentioning
confidence: 99%
“…In a systematic review of trial data on BCG effectiveness, the variation in background intensity of Mtb transmission seems to be able to explain the considerable heterogeneity of BCG vaccination, with sustained protection more evident in settings with lower transmission rates. 30 In line with this hypothesis, in a study among household contacts of individuals with sputum-smear-positive pulmonary TB disease in Indonesia, protection of BCG against infection was found to be stronger in individuals with lower levels of exposure. These data support the hypothesis that higher exposure to Mtb, which is more common in areas with high TB prevalence, may overcome protection induced by BCG and explain variation between geographical areas.…”
Section: Bcg Vaccinationmentioning
confidence: 85%